A NONLINEAR FACTOR ANALYSIS FOR LARGE SETS OF MACROECONOMIC TIME SERIES - Mendes, D. A.; Mendes, V. (JuliaCon2019, 2019)
Dynamic factor models are frequently used for empirical research in macroeconomics. Several papers in this area have argued that the co-movements of large panels of macroeconomic and financial data can be captured by a relatively few common unobserved (latent) factors. The main purpose of this paper is to analyze and compare the transmission mechanism of monetary policy in the USA, by using a FAVAR model based on two different approaches, in order to include information from large data sets. The first approach consists of a classical linear methodology where the factors are obtained through a principal component analysis (PCA), while the second one employs a nonlinear factor algorithm based on independent component analysis (ICA) and on a Nonlinear PCA. In comparison to PCA, the factors extracted by nonlinear methods provide a better performance in the Factor Augmented VAR model, which can be illustrated by Impulse Response Functions and forecasting. We perform the dynamic inference on the model by using a dynamic bayesian estimation.